Emerging roles of calcium-sensing receptor in the local regulation of intestinal transport of ions and calcium - Krittikan Chanpaisaeng (2022)
Whether the intestinal mucosal cells are capable of sensing calcium concentration in the lumen and pericellular interstitium remains enigmatic for decades. Most calcium-regulating organs, such as parathyroid gland, kidney, and bone, are capable of using calcium-sensing receptor (CaSR) to detect plasma calcium and trigger appropriate feedback responses to maintain calcium homeostasis. Although both CaSR transcripts and proteins are abundantly expressed in the crypt and villous enterocytes of the small intestine as well as the surface epithelial cells of the large intestine, the studies of CaSR functions have been limited to amino acid sensing and regulation of epithelial fluid secretion. Interestingly, several lines of recent evidence have indicated that the enterocytes use CaSR to monitor luminal and extracellular calcium levels, thereby reducing the activity of transient receptor potential channel, subfamily V, member 6, and inducing paracrine and endocrine feedback responses to restrict calcium absorption. Recent investigations in zebra fish and rodents have also suggested the role of fibroblast growth factor (FGF)-23 as an endocrine and/or paracrine factor participating in the negative control of intestinal calcium transport. In this review article, besides the CaSR-modulated ion transport, we elaborate the possible roles of CaSR and FGF-23 as well as their crosstalk as parts of a negative feedback loop for counterbalancing the seemingly unopposed calciotropic effect of 1,25-dihydroxyvitamin D3 on the intestinal calcium absorption.